HAS NEPENTHES PITOPANGII CHI C. LEE, S. MC PHERSON, BOURKE & M. MANSUR A RARE AND ENDEMIC FLOWERING PLANT OF SULAWESI, BEEN EXTINCT IN ITS ORIGINAL NATURE? - Pitopang, Ramadhanil; Thaha, Irmasari; Amar, Andi Lagaligo; Lee, Chien C. (Natural Science: Journal of Science and Technology, 2018)
Nepenthes pitopangii Chi C. Lee, Mc Pherson, Bourke & M. Mansur  (Nepenthaceae), is an  endemic pitcher plant to  Sulawesi. The population of this plant at its type locality  is only two individuals,  on the other hand   human activities like rattan and dammar collecting  by local community and  ecotourism  activity  have contributed to a   decline in the population. The purpose of this research is to assess the current condition of the habitat of Nepenthes pitopangii at its type locality   in  Lore Lindu National Park. Field work was done in the period of September  2016-September 2017. The vegetation of Nepenthes pitopangii habitat was studied  by using botanical exploration methods.  The result showed that both location  had been heavily damaged due to habitat human activities with no further evidence of the precense of N pitopangii at either site. Additionally, We noted  a number of plant species arround the  habitat which were widespread in montain forest of Lore Lindu National Park such as Xanthomyrtus angustifolia (Myrtaceae), Weinmania lucens (Cunoniaceae), Vaccinium  palawanensis (Ericaceae), Phyllocladus hypophylus (Podocarpaceae), Drymis piperita (Proteaceae), Gleichenia vulcanica, Stricherus truncatus, Lycopodiella cernua and Dicksonia blumei